The effect of fructosamine 3 kinase (FN3K) genotypes on the glycation gap in type 2 diabetic and non-diabetic mixed ancestry population of South Africa - Motshwari, Dipuo Dephney (Stellenbosch : Stellenbosch University, 2018)
Thesis (MMed)--Stellenbosch University, 2018.